2020
DOI: 10.3390/ani10081311
|View full text |Cite
|
Sign up to set email alerts
|

Effects of A Concentrate Rich in Agro-Industrial By-Products on Productivity Results, Carcass Characteristics and Meat Quality Traits of Finishing Heifers

Abstract: Finishing diets in intensive beef production systems are mainly based on cereals, which does not take advantage of the capacity of the ruminant digestive system to digest fibrous feeds, cannot be considered sustainable and does not contribute to the circular bioeconomy. Our aim was to investigate the effects of an alternative concentrate rich in agro-industrial by-products for finishing crossbred Limousine heifers. Four pens with 12 heifers and four pens with 13 heifers were randomly allocated to one of two tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 37 publications
(53 reference statements)
3
9
1
Order By: Relevance
“…The juiciness scores were similar between diets, which agrees with the results obtained by Moreno-Diaz et al [17] when analyzing the water-holding capacity (drip and cooking losses) in the same animals of the current study, although the connection between cooking loss and juiciness is not simple.…”
Section: Sensory Analysissupporting
confidence: 92%
See 3 more Smart Citations
“…The juiciness scores were similar between diets, which agrees with the results obtained by Moreno-Diaz et al [17] when analyzing the water-holding capacity (drip and cooking losses) in the same animals of the current study, although the connection between cooking loss and juiciness is not simple.…”
Section: Sensory Analysissupporting
confidence: 92%
“…These results complement those obtained by Moreno-Diaz et al [17], who reported that the alternative diet did not present negative effects on growth performance or carcass and meat traits. However, it is possible that the alternative diet might have induced small variations in meat traits that affected sensory characteristics (such as color or flavor) and were not detected by Moreno-Díaz et al [17] (i.e., due to sensitivity of the instrumental techniques, variability between experimental units, etc.) but did not pass unnoticed by regular users who have enough experience to detect small variations in sensory characteristics.…”
Section: Sensory Analysissupporting
confidence: 91%
See 2 more Smart Citations
“…Further support for use as animal feed comes from [137], in which E-LCA and life-cycle costing applied to different valorisation alternatives for food waste showed that use as animal feed is environmentally and economically more attractive than the conversion to organic acids. Using agro-industrial by-products as animal feed, to replace a part of the cereals fed to beef cattle, did not affect the quality of the meat in any way, as shown by Diaz et al (2020) [72]. Part of the animal feed manifests as manure which again is a biorefinery input.…”
Section: Municipal and Industrial Solid Waste And Sewage Managementmentioning
confidence: 83%